STRATEGY FORMULATION FOR EXTRUCK COFFEE TOMOHON - Wuner, Juninho; Mangantar, Marjam; Rogi, Mira (Universitas Sam Ratulangi, 2024)
The aim of this research is to examine Extruck internal and external environment and to formulate business strategy for Extruck Coffee. This study is a combination of qualitative and quantitative analytical methods. Additional quantitative methods in this study are intended to support the analytical process, using the role of quantitative analysis to facilitate qualitative research by using strategy formulation analytical tools such as IFE, EFE, CPM, SWOT, IE, Grand Strategy, SPACE and QSP matrices. The IFE and EFE matrix reveal the main factors that influence Extruck Coffee. Quality, Price, and Brand Image being the main key strength of Extruck Coffee. Extruck possessed several weaknesses regarding to its Location, Place Attractiveness, Sales, and Promotion. The main key opportunities that occur in its industry is the behavior of people that being consumptive toward coffee product also severe threats that occurs from number of existing competitor and control over supplier. The result of QSP Matrix stated that Market Development is the most appropriate strategy to implement by Extruck Coffee with the total score point of 4.66. Keywords: Strategy Formulation, IFE, EFE, CPM, SWOT, IE, Grand Strategy, SPACE matrix, QSPM